Developing GROUPS Model for Learning English Communication Skills: Kamphaeng Phet Rajabhat University, Maesot - Praimahaniyom, Thirawit; Chairinkom, Banjong (Trends of Humanities and Social Sciences Research, 2020)
This study aimed 1) to develop GROUPS Model for learning English communication skill, 2) to investigate the effectiveness of the GROUPS Model in developing learners’ English communication skill and 3) to identify the students’ satisfaction towards GROUPS Model at Kamphaeng Phet Rajabhat University, Maesot. The subjects were two groups; the first group, in a needs assessment step, consisted of 11 experts from different universities, 256 English students and 124 English graduates of Kamphaeng Phet Rajabhat University, 51 English teachers, and 71 employers in Maesot District, Tak Province via simple and convenient technique samplings. The second group, in a pilot study step, composed of 35 learners, including; 18 Accounting students, 17 English students via a simple random in the 2nd semester, the academic year of 2016 at Kamphaeng Phet Rajabhat University, Maesot. The research tools were a needs assessment questionnaire, an achievement test and a questionnaire. Quantitative data was analyzed using descriptive statistics: Mean ( ), and Standard Deviation (S.D.) while the content analysis was applied for qualitative one. The findings were as follows. 1) To develop GROUPS Model for learning English communication skill, it indicated that needs assessment in overall it was at “High” (x=3.56) while the experts’ opinions towards the GROUPS Model and lesson plan were at “Most congruence” (x=4.44 and 4.47). 2) To investigate the effectiveness of the GROUPS Model, it revealed that the GROUPS Model achievement test mean scores, in overall it was at “Good” (x=2.56), and the English performance achievement test mean scores in overall it was at “Good” (x=2.81). 3) To identify the students’ satisfaction towards GROUPS Model, it discovered that in overall it was at “High” (x=3.63).